Edukasi Video Directly Observed Therapy sebagai upaya Tingkat Kepatuhan Pengobatan Tuberkulosis di Kota Depok - Hendro Purwadi; Umar Ruswandi; Teti Rahmawati; Lia Fitriyani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2026)
Indonesia currently has the second-highest number of TB cases in the world, ranking second. The highest number of TB cases is reported from provinces with large populations, namely West Java, East Java, and Central Java. Depok City is one of the contributors to the TB burden in West Java. Based on the estimated TB burden data for the entire West Java Province, Depok City ranks 7th with an estimated 3,853 cases. Video Directly Observed Therapy (VDOT) is a technique that uses video monitoring to ensure that patients take their medication as prescribed; this strategy is considered more effective than directly observed therapy. This study uses a quasi-experimental design. This community service activity was conducted in Depok City in May 2025. The number of participants in this activity was 30 respondents, divided into an intervention group of 15 people and a control group of 15 people. The intervention group was monitored through video directly observed therapy for 8 weeks, while the control group underwent conventional monitoring. Data were collected through questionnaires. The study results showed that directly observed therapy education was effective in improving tuberculosis treatment (p value = 0.000).